2003
DOI: 10.1002/jmv.10468
|View full text |Cite
|
Sign up to set email alerts
|

Determination of HBsAg subtypes in Western Siberian part of Russia

Abstract: A set of monoclonal antibodies with specificity for hepatitis B surface antigen (HBsAg) was used for subtyping this antigen in sera from indigenous natives, blood donors, and drug users in Western Siberia with a modified commercial enzyme immunoassay kit for HBsAg detection. Three subtypes of HBsAg in a ratio of 36 (78%) ayw2:8 ayw3varB (18%):2 (4%) adw2 were found in 46 (100%) HBsAg-positive sera of different aboriginal populations of Western Siberia: the Tundra Nenets, Northern Khanty, Southern Altaians, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
1
4
0
3
Order By: Relevance
“…In Western Siberia, the genotype D constitutes even more than 96 % of the total. In contrast to Latvia, the ayw2 subtype was clearly predominant over the ayw3 subtype [47]. Our data also support the postulate, that genotype D is predominant in the Mediterranean region, Southern and Eastern Europe, in such countries as Hungary [48], Italy: 73% of the genotype D, and 26% of the genotype A [49,50], and Spain: 63,2% and 23.1%, respectively [51,52].…”
Section: Hbv Genotypes In Latvia and Neighboring Countriessupporting
confidence: 77%
“…In Western Siberia, the genotype D constitutes even more than 96 % of the total. In contrast to Latvia, the ayw2 subtype was clearly predominant over the ayw3 subtype [47]. Our data also support the postulate, that genotype D is predominant in the Mediterranean region, Southern and Eastern Europe, in such countries as Hungary [48], Italy: 73% of the genotype D, and 26% of the genotype A [49,50], and Spain: 63,2% and 23.1%, respectively [51,52].…”
Section: Hbv Genotypes In Latvia and Neighboring Countriessupporting
confidence: 77%
“…Thus, all genotype A strains specified adw2, the single strain specifying adrqþ belonged to genotype C. The most prevalent subtypes in genotype D were ayw3 and ayw2 with a tendency to segregation into separate clusters. Using a panel of monoclonal antibodies Netesova et al [2003] reported a 94% prevalence of ayw3variantA in drug users. While this subtype was found in 11% of blood donors it was absent in the native population of West Siberia.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, similar studies that used samples obtained before national hepatitis B immunization programs were launched (2001 [41]) yielded lower estimates of herd immunity. Thus, [75,76] …”
Section: Seroepidemiological Studiesmentioning
confidence: 99%